Spinal Intradural Hematoma Following Neuraxial Anesthesia in a Uroseptic Patient: A Case Report and Narrative Review - Bihariesingh-Sanchit, Rosita; Sewkaransing, Dirani; Ma, Rocade; Amsari, Marciano; Ramsoekh, Anand; Mawie, Terrence; Bergen, Yigal; Somai, Shivani; Joe, Rudie Tjong Tjin (Brazilian Journal of Case Reports, 2026)
Spinal intradural hematoma (SIH) is a rare but potentially devastating complication of neuraxial anesthesia, particularly in critically ill patients with sepsis-associated thrombocytopenia and coagulation abnormalities. A 63-year-old woman presented with septic shock secondary to obstructive uropathy caused by ESBL-producing Klebsiella pneumoniae. Initial management included intravenous fluid resuscitation, vasopressor support, antimicrobial therapy, and urinary decompression. Following transient hemodynamic stabilization, she underwent urological intervention under spinal anesthesia. Retrospective review demonstrated thrombocytopenia (63 ×10⁹/L) on the day of the procedure, which had not yet been recognized at the time of anesthesia. Within 24 hours, the patient developed acute bilateral lower limb weakness and sensory deficits. Magnetic resonance imaging (MRI) confirmed spinal intradural hematoma at the L2–L3 level with significant neural compression. Emergency decompressive laminectomy was performed; however, neurological recovery remained incomplete. This case highlights the importance of continuous reassessment of coagulation parameters in critically ill septic patients undergoing neuraxial procedures. New neurological deficits following neuraxial anesthesia should be regarded as a medical emergency requiring immediate imaging and urgent neurosurgical evaluation.